An Energy-aware Dynamic Data Allocation Mechanism for Many-channel Memory Systems - Sato, Masayuki; Toyoshima, Takuya; Takayashiki, Hikaru; Egawa, Ryusuke; Kobayashi, Hiroaki (Supercomputing Frontiers and Innovations, 2020)
A modern memory system is equipped with many memory channels to obtain a high memory bandwidth. To take the advantage of this organization, applications’ data are distributed among the channels and transferred in an interleaved fashion. Although memory-intensive applications benefit from a high bandwidth by many memory channels, applications such as compute-intensive ones do not need the high bandwidth. To reduce the energy consumption for such applications, the memory system has low-power modes. During no memory request, the main memory can enter these modes and reduce energy consumption. However, these applications often cause intermittent memory requests to the channels that handle their data, resulting in not entering the low-power modes. Hence, the memory system cannot enter the low-power modes even though the applications do not need the high bandwidth. To solve this problem, this paper proposes a dynamic data allocation mechanism for many-channel memory systems. This mechanism forces data of such applications to use the specified channels by dynamically changing the address-mapping schemes and migrating the data. As a result, the other channels to which the data are not allocated can have a chance to enter the low-power modes for a long time. Therefore, the proposed mechanism has the potential to reduce the energy consumption of many-channel memory systems. The evaluation results show that this mechanism can reduce the energy consumption by up to 11.8% and 1.7% on average.